Geographic vision of the perception of risks due to extreme hydrometeorological hazards in Cuba - Bayón-Martínez, Pablo; Padilla y Sotelo, Lilia Susana (Revista Geográfica de América Central., 2019)
Geographical knowledge is the basis for the theoretical and practical construction of space as a conception of the environment, as well as for the necessary environmental cultural formation of social actors in the contexts of production and reproduction of life. The understanding of the geographical particularities of the space where the daily life of the individual elapses contributes to the perception of the risks brought by extreme hydrometeorological hazards. The article is the result of the analysis, from a geographical perspective, of the study of Cuba’s national perception of risks from hydrometeorological hazards for the period 2009-2011, with the inclusion of related thematic maps. It aims at contributing to Cuba’s Environmental Agency efforts in environment social studies, risk management of disasters and local geographic education. Keywords: Hydrometeorological hazards; Risk perception; Social vulnerability; Environmental cultural formation; Geographical education.